A Study on the Fabrication of Seamless Semiconducting and Metallic Nanowire Networks and their Applications for Transparent Electronics - SHEERIN, EMMET (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2020)
Devices based on individually contacted 1-D nanostructures have demonstrated high performance across a wide variety of applications, however commercial scale production of these devices is limited by tedious and costly direct-write lithography processes required for their fabrication. Networks of randomly oriented individual nanowires have been investigated as more scalable alternatives, but large contact resistances present at nanowire junctions result in decreased device performance. This work details the development of top-down templating techniques for the fabrication of interconnected nanowire networks with seamless junctions and investigates their optoelectronic performance. Continuous silicon nanowire networks are fabricated from a silicon-on-insulator precursor and investigated as transparent photodetectors. A colloidal crack lithography process is exploited to pattern a silicon device layer with an interconnected metal network which is used as an etch mask to map down the seamless structure onto the underlying silicon film. Removal of the metal material is achieved through a series of selective chemical etches. The silicon network is mounted on a transparent and flexible PET substrate using a float transfer process and localised regions of porous silicon are introduced into the crystalline network structure through a HF/H2O2 metal assisted chemical etch. The PET mounted network shows high transparency across the visible spectrum as well as stability under flexing tests and demonstrates comparable performance to the best reported transparent photodetectors from literature. Low temperature studies showed evidence for a variable range hopping mechanism and the observed photoconduction behaviour was attributed to charge carrier hopping between localised trap states. A process for the formation of a deposition template mapped from the structure of electrospun nanofibres is described and the performance of templated aluminium nanowire networks as transparent conductors is investigated. Optimisation of an electrospinning process for bead free PMMA nanofibres is detailed and a pattern transfer technique exploiting the orthogonal solubilities of PMMA and PS in combination with a line of sight metal deposition process is developed. The final template structure is realised through an oxygen plasma etch and the high fidelity of this pattern transfer process is demonstrated through SEM analysis of the PMMA nanofibres and the templated metal structures. Fabricated aluminium networks display comparable performance to the current best transparent conductor materials from literature. These networks are notably the first aluminium based materials to outperform thin films of indium tin oxide, the current industry standard transparent conductor. These aluminium nanowire networks also offer a lower raw material cost and demonstrate superior corrosion stability against atmospheric sulfur compounds than silver nanowire networks.
APPROVED